Automated bone property analysis using corrected in vivo dental cone-beam CT data of human wrists - Benjamin Klintström; Anna Spångeus; Alexandr Malusek; Alexander Synek; Mischa Woisetschläger; Dieter Pahr; Eva Klintström (Scientific Reports)
Abstract Fracture liaison services are essential to mitigate underdiagnosis and undertreatment of osteoporosis-related fractures. However, it often suffers from limited access to dual-energy X-ray absorptiometry (DXA) or high-resolution peripheral quantitative CT equipment. This in vivo study of 21 patients aims to evaluate the feasibility of dental cone beam CT (dCBCT) to analyse bone properties of human wrists, comparing with DXA and finite element (FE) analysis. dCBCT grey-scale values were transformed to HU using a phantom containing materials with known HU values. Strong correlations were found between bone mineral content (BMC) from dCBCT and DXA (r = 0.78 to 0.84, p < 0.001), as well as between BMC from dCBCT FE-predicted stiffness (r = 0.91) and maximum force (r = 0.93), p < 0.001. BMC values from dCBCT were higher than DXA measurements (2.34 g vs. 1.5 g, p < 0.001). Cortical thickness strongly correlated to bone mineral density (BMD) from dCBCT (r = 0.83, p < 0.001). No statistically significant correlations were found between trabecular bone microstructure and FE predictions. The results indicate the feasibility to analyse osteoporosis related bone properties of human wrists from corrected dCBCT data. The dCBCT values of BMD and BMC were strongly correlated with DXA.